Akuntansi Sosial: Analisis Social Return on Investment (SROI) pada Social Bussiness Studi Kasus pada Kelompok Tani Kopi Republik Tani Mandiri - Audito, Audito Aji Anugrah; Aliyanti, Nabila Maulina Delia; Cahyadi, Rino Tam; Stephanus, Daniel Sugama (Jurnal Akuntansi AKUNESA, 2024)
This research aims to prove the effectiveness of an social business through a social accounting approach using the Social Return on Investment (SROI) instrument. This research was conducted at the Republik Tani Mandiri (RTM) Coffee Farmers Group, which is a social business in the field of coffee farming. This research approach uses a mixed method research type using an advanced exploratory approach using instruments from Social Return on Investment. The results of the Social Return on Investment (SROI) calculation for this group show a figure of 1:0.20. The results of this research show that every investment made produces a multiple impact. The Republic of Tani Mandiri (RTM) Coffee Farmers Group has succeeded in creating significant social, economic and environmental impacts for various Stakeholders. This indicates that Republik Tani Mandiri (RTM) is efficient in creating added value for Stakeholders. This cannot be separated from the importance of collaboration, support from the government and universities plays an important role in optimizing the implementation and management of Republik Tani Mandiri (RTM) to achieve common goals. It is hoped that these findings will encourage Stakeholders to continue to support similar investments in the future to improve community welfare